2021
DOI: 10.3390/ijms22020968
|View full text |Cite
|
Sign up to set email alerts
|

The Functions of the Demethylase JMJD3 in Cancer

Abstract: Cancer is a major cause of death worldwide. Epigenetic changes in response to external (diet, sports activities, etc.) and internal events are increasingly implicated in tumor initiation and progression. In this review, we focused on post-translational changes in histones and, more particularly, the tri methylation of lysine from histone 3 (H3K27me3) mark, a repressive epigenetic mark often under- or overexpressed in a wide range of cancers. Two actors regulate H3K27 methylation: Jumonji Domain-Containing Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 113 publications
0
13
0
Order By: Relevance
“…In this study, we demonstrated that JMJD3 and H3K27me3 have a role in prostate cancer progression.H3K27me3, whose demethylation is regulated by JMJD3, was found to be underor over-expressed in a wide range of cancers (29). This study aims to identify the impact of JMJD3 inhibition by its inhibitor, GSK4, on prostate tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we demonstrated that JMJD3 and H3K27me3 have a role in prostate cancer progression.H3K27me3, whose demethylation is regulated by JMJD3, was found to be underor over-expressed in a wide range of cancers (29). This study aims to identify the impact of JMJD3 inhibition by its inhibitor, GSK4, on prostate tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…JMJD3 is often over or under expressed in a large variety of cancers including, but no limited to nervous system, prostate, blood, colorectal, breast, lung, liver, ovarian, gastric cancers. This makes the demethylase difficult to classify as a tumor suppressor or oncoprotein (29).…”
mentioning
confidence: 99%
“…Combined with the existing literature, we speculate that this may be related to the methylation of H3K27me3 at the promoter of this gene; PTEN has been demonstrated to promote the expression of CTNNA1 and thus inhibit myeloproliferation. The role of other pathways, such as JMJD3 and HOX [48], associated with CTNNA1 still needs to be further validated (Fig. 3A).…”
Section: Role Of Ctnna1 In Hematologic Malignanciesmentioning
confidence: 99%
“…80 The genomic instability that emerges and propagates during the expansion of malignant clonal prostate cancer cells likely creates a fertile environment for genetic disruption of these chromatin regulators. These chromatin regulatory enzymes are being considered as therapeutic targets for small molecule inhibition in several cancers, 81 including prostate cancer. 82,83 Thus, small molecule inhibitors targeting individual BET bromodomain proteins, in combination with inhibitors of other chromatin regulators, represent an innovative approach to solve the problem of emerging ADT-resistant forms of prostate cancer.…”
Section: Chromatin Regulators In Mechanisms Of Emt and Chemoresistancementioning
confidence: 99%